2011
DOI: 10.1128/jvi.00290-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Editing of Herpes Simplex Virus 1 and Epstein-Barr Herpesvirus Genomes by Human APOBEC3 Cytidine Deaminases in Culture and In Vivo

Abstract: The seven-gene human APOBEC3 (A3) cytidine deaminase locus came to the fore with the identification of APOBEC3G (A3G) as the interaction partner of the human immunodeficiency virus (HIV) Vif protein (8,16,26,29,30,43,57). These enzymes belong to a larger group that can edit nucleic acids, of which activation-induced cytidine deaminase (AICDA), responsible for class switch recombination and somatic hypermutation of rearranged immunoglobulin V region genes, is perhaps the most widely known (11). All functional A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 57 publications
3
144
0
2
Order By: Relevance
“…The same strategies used by restriction factors to block retroviruses may also be employed to limit infection of DNA viruses. For example, both the APOBEC3 and tetherin/BST2 proteins have been suggested to inhibit herpesvirus infection (19,20). The human SAMHD1 protein was recently identified as a retroviruses restriction factor (8,9).…”
mentioning
confidence: 99%
“…The same strategies used by restriction factors to block retroviruses may also be employed to limit infection of DNA viruses. For example, both the APOBEC3 and tetherin/BST2 proteins have been suggested to inhibit herpesvirus infection (19,20). The human SAMHD1 protein was recently identified as a retroviruses restriction factor (8,9).…”
mentioning
confidence: 99%
“…To control massively activated LINE-1, germ line cells express a special type of small RNA named piRNA (piwi-interacting RNA) that arms Piwi (P-element induced wimpy testis) proteins to suppress LINE-1 (25,26). Furthermore, it has been reported that APOBEC3 (apolipoprotein B mRNA-editing, enzyme-catalytic, polypeptide-like 3) proteins, which inhibit the infection of a broad range of viruses particularly retroviruses (27)(28)(29)(30)(31), also provide another mechanism to control LINE-1 (32)(33)(34). It appears that cells manage to use the same mechanism to protect themselves from either extracellular or intracellular insults that share common biochemical features.…”
mentioning
confidence: 99%
“…A3A, A3G, and activation-induced cytidine deaminase (AICDA) can edit what is thought to be a small fraction of HSV genome in an experimental setting without seriously impacting viral titers. Hyper-editing was found to occur in HSV genomes recovered from four of eight uncultured buccal lesions, but the phenomenon was not restricted to HSV; hyper-mutated EBV genomes were readily recovered from four of five established cell lines, indicating that episomes are also vulnerable to editing 67 . These findings suggest that the widely expressed A3C cytidine deaminase can function as a restriction factor for some human herpesviruses.…”
Section: Mutation Of the Ebv Genome Affects Encoded Mirnasmentioning
confidence: 97%
“…66 Mechanistic analysis of this sequence variability has recently been reported by Suspène et al 67 Human APOBEC3 cytidine deaminases target and edit singlestranded DNA, which can be of viral, mitochondrial, or nuclear origin. Retroviral genomes, such those of HIV, deficient in the vif gene, and hepatitis B virus, are particularly vulnerable.…”
Section: Mutation Of the Ebv Genome Affects Encoded Mirnasmentioning
confidence: 99%